2017
DOI: 10.1007/s11666-017-0662-2
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution in Solution Heat Treatment of Gas-Atomized Al Alloy (7075) Powder for Cold Spray

Abstract: Cold gas dynamic spray is being explored as a repair technique for high-value metallic components, given its potential to produce pore and oxide-free deposits of between several micrometers and several millimeters thick with good levels of adhesion and mechanical strength. However, feedstock powders for cold spray experience rapid solidification if manufactured by gas atomization and hence can exhibit non-equilibrium microstructures and localized segregation of alloying elements. Here, we used sealed quartz tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…As a result, this method is categorized Figure 11. Top: SEM micrographs of cold spray-coated AA6061 substrate by (a) as-received and (b) heat-treated AA7075 particles with a mechanical interlocking between the coating and the substrate [105]. Bottom figure: a schematic view of cold spray coating process [106].…”
Section: Cold Spray Coatingmentioning
confidence: 99%
“…As a result, this method is categorized Figure 11. Top: SEM micrographs of cold spray-coated AA6061 substrate by (a) as-received and (b) heat-treated AA7075 particles with a mechanical interlocking between the coating and the substrate [105]. Bottom figure: a schematic view of cold spray coating process [106].…”
Section: Cold Spray Coatingmentioning
confidence: 99%
“…Because features in the powder are retained during consolidation, the as-atomized microstructure can be controlled using thermal treatments. Recent research has shown the retention of feedstock powder microstructure during consolidation for other alloys, though that research included a limited analysis of the internal microstructure of the powders, not fully investigating the effect of the thermal treatments on the powders [10][11][12][13][14]. These researchers assumed the network of solute elements at the boundaries in the as-atomized structure, as seen in scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS), was segregation.…”
Section: Introductionmentioning
confidence: 99%
“…Solutionization times for Al 7075 are typically on the order of 4-16 h for wrought components, depending on part size [9]. Given this timescale, other researchers chose to use long heat treatment times for their powders; however, other researches performed on Al 6061 indicated faster diffusion times in powders, resulting in the need for shorter thermal treatments [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, Sabard et al applied a heat treatment to the as-atomized powders prior to use in cold spray consolidation. 7 They found that, with a heat treatment of 4 h at 450°C, particle deformation was enhanced, leading to improved particle-substrate bonding and thicker coatings. Additionally, they found that the thermally-treated powders had a reduction in solute segregation and a higher porosity than the as-atomized condition.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, with the advent of AM, the focus was first on creating the process and then on optimizing the processing parameters for the consolidated part, and it is only in recent years that research has been conducted analyzing the effects of the feedstock on the consolidated parts. [3][4][5][6][7][8][9][10] Many metal AM techniques that utilize powder as feedstock employ melting as a means of consolidating the feedstock into a solid material. These processes use different methods to melt the feedstock, for example, electron beams or lasers, which affect the melt pool temperature, 11,12 and differences in melt pool temperature can influence the microstructure.…”
Section: Introductionmentioning
confidence: 99%